SAND, George. François, o menino abandonado. Tradução de Liliana Mendonça. Revisão de Lucia Peixoto Cherem. São Paulo: Kazuá, 2017, 92 p. - Menezes, André Luís Leite de; Bigaton, Jaqueline Sinderski (Cadernos de Tradução, 2020)
SAND, George. François, o menino abandonado. Tradução de Liliana Mendonça. Revisão de Lucia Peixoto Cherem. São Paulo: Kazuá, 2017, 92 p.